High tank dual canal system: an innovative approach of water allocation for a water scarce region - Wijerathna, Deeptha; Jayakody, Priyantha (2007)
This paper discusses the importance of equitable water allocation for all farmers of an irrigation system. It addresses the potential and relevance of high tank dual canal systems for equitable allocation of scarce land and water resources to alleviate poverty. Recent irrigation settlement projects in Sri Lanka have significantly contributed to poverty alleviation. Yet, a considerable number of farm households in these settings face transient or chronic poverty while some others are well off. Inequities of resource allocation and inefficiencies in resource use are two main reasons for this. In a given agricultural settlement potential for crop production is not unique to all parts of the land. It varies with soil conditions, terrain, elevation and ease of obtaining irrigation water. Availability of water for tail-enders depends on total stock of water available in the system as well as usage of head-enders. Although all farmers would prefer land at the head end, with the increasing pressure on land more and more people have had to be settled at the tail end. Further, lands that were once abandoned due to low productivity, difficulties in irrigation etc have also had to be used by utilizing alternative technologies. Another problem that features in the Sri Lankan contest is almost all farmers have a tendency to cultivate staple food of rice in their fields. Rice needs huge amounts of water compared to other crops and when unsuitable lands are used, it results in huge losses. Uda Walawe Irrigation project in Sri Lanka is a water-short irrigation system which has hardly enough water to irrigate its total command area. This has forced downstream developers to come up with innovative ways of water allocation to ensure equitable amounts of water for all farmers in the command area. The high-tank dual canal system introduced under the extension and rehabilitation project of the Walawe left bank is one novel approach which attempts to maximize resource use with equitable distribution. It helps to solve two basic resource based conflicts; demand for water and fertile land. Tanks with this system consists of four main canals; two each from left and right banks, instead of only two main canals in conventional system. Two canals; one from each bank is allocated to provide water for paddy lands while the other two canals provide water for non paddy crops. The quantity of water release and the interval of water release are low for the non paddy crops. Firstly, this new system reduces conflicts among farmers within the command area for water and land allocation. Secondly, planned and careful water use of these farmer groups release some water for some other water uses of the tail end of the main irrigation system. This paper analyzes the potential of new approach in saving water and providing equitable allocation of land and water resources. It estimates level of poverty with and without new technique to analyze the relevance of the approach in reducing poverty with equitable income distribution.